Mental Disorders Are Associated With Leukocytes Telomere Shortening Among People Who Inject Drugs - Durand, Mélusine; Nagot, Nicolas; Michel, Laurent; Le, Sao Mai; Duong, Huong Thi; Vallo, Roselyne; Vizeneux, Amélie; Rapoud, Delphine; Giang, Hoang Thi; Quillet, Catherine; Thanh, Nham Thi Tuyet; Hai Oanh, Khuat Thi; et al. (Frontiers in Psychiatry, 2022)
Premature biological aging, assessed by shorter telomere length (TL) and mitochondrial DNA (mtDNA) alterations, has been reported among people with major depressive disorders or psychotic disorders. However, these markers have never been assessed together among people who inject drugs (PWIDs), although mental disorders are highly prevalent in this population, which, in addition, is subject to other aggravating exposures. Diagnosis of mental disorders was performed by a psychiatrist using the Mini International Neuropsychiatric Interview test among active PWIDs in Haiphong, Vietnam. mtDNA copy number (MCN), mtDNA deletion, and TL were assessed by quantitative PCR and compared to those without any mental disorder. We next performed a multivariate analysis to identify risk factors associated with being diagnosed with a major depressive episode (MDE) or a psychotic syndrome (PS). In total, 130 and 136 PWIDs with and without psychiatric conditions were analyzed. Among PWIDs with mental disorders, 110 and 74 were diagnosed with MDE and PS, respectively. TL attrition was significantly associated with hepatitis C virus-infected PWIDs with MDE or PS (adjusted odds ratio [OR]: 0.53 [0.36; 0.80] and 0.59 [0.39; 0.88], respectively). TL attrition was even stronger when PWIDs cumulated at least two episodes of major depressive disorders. On the other hand, no difference was observed in mtDNA alterations between groups. The telomeric age difference with drug users without a diagnosis of psychiatric condition was estimated during 4.2–12.8 years according to the number of MDEs, making this group more prone to age-related diseases.